Performance of BARI ghom26 Under Saline Stressed Condition (Journal of Environmental Science and Natural Resources, 2015)
A pot experiment was carried out to study the performance of BARI ghom26 under saline stressed condition in order to find out the optimum salinity level for cultivation. The study was consists of three salinity stressed levels viz. 4.0, 8.0 and 12.0 dS m-1 together with a control 0.0 dSm-1 for the observing the field performance under saline stressed condition of Patuakhali while salinity was applied in 45 Days After Sowing (DAS). This study also revealed plant height, leaf area index, stem dry weight pant-1, shoot dry weight pant-1, root dry weight pant-1, total dry matter pant-1, number of effective tillers hill-1 , length of spike (cm), ,number of grain spike-1 , 1000 grain weight (g), grain yield plant-1, shoot yield plant-1, yield ha-1, harvest index and grain nutrient percentage were gradually decreased with continuing increased in salinity levels. Grain Na percentage reveled the antagonistic salinity effect on N P K absorbance. On the other hand, 4.0 dSm-1 salinity found to be the considerable tolerance level for cultivating the BARI ghom26 under saline stressed condition of Patuakhali.DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22160 J. Environ. Sci. & Natural Resources, 7(1): 127-130 2014